Problematic and Solution in Memorizing the Al-Qur'an in Al-Muqodasah Islamic Boarding Schools Ponorogo Indonesia - Heru Saiful Anwar; Alhumam Abdul Mundzir (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Abstract: Beginning of the establishment of al-Muqodasah Islamic boarding school was only focused on memorizing the Qur'an alone, then a few years later it was required for public schools so that the students' learning time was reduced, so that problems arose in memorizing the Qur'an. The purpose of this essay is: Knowing the problem of memorizing the Qur'an, knowing how problem solving solves the Qur'an. This research is descriptive qualitative, the data collection techniques used are: Interview menthod, observer method, dokumentary method. The results of the study are as follows: The problem of memorizing the Qur'an is: Feeling lazy, having problems from the teacher, having problems with friends, having broken home problems. the needs of student are not fulfilled. Solving the problem of memorizing the Qur’an is: The teacher must be more creative so that the santri do not lazily memorize the Qur’an such as punishing those who are sleepy or sleeping, can also motivate students to occasionally not feeling bored, the teacher was required to arrive on time in order to control the student in memorizing the Qur'an, because if they were late or even not coming then the santri would carry out activities as they pleased because no one was in control, It is expected that all santri will forgive each other's mistakes, it is unlawful for parens to report to student about problems from his house, It is expected that all parens to complete their children's needs are lodged.Keywords: Al-Qur’an, teacher, student, problematic, solution. ملخص: بداية إنشاء المعهد المقدسة في عام 1992، في ذلك الوقت فقد درس المعهد، ولم تكن هناك مدرسة ابتدائية أو متوسطة أو ثانوية في المعهد، في عام 2010 كان هناك مدرسة ابتدائية أو متوسطة أو ثانوية في المعهد، فوجب بمدير المعهد لدخول تلك المدرسة في المعهد علي فصله،. أنّ زيادة الوقت لتعلّم وينقص لتحفيظ القرآن كان ظهر قضايا حفظ القرآن الكريم في معهد المقدسة فونوروكو. وأهداف البحث في هذا البحث هو: الكشف عن قضايا حفظ القرآن، الكشف عن كيف حلّ قضايا حفظ القرآن. فكان هذا البحث من بحث الكيفي، وكان البحث من نوع الدراسة الميدانية الوصفية، وللحصول على ما يحتاج إليه من المواد استخدم الباحث بثلاثة طرق هي: الملاحظة لالكشف عن النظام، والكشف عن كيف حلّ قضايا حفظ القرآن ،المقابلة لالكشف عن حلّ قضايا حفظ القرآ الكريم في معهد المقدسة فونوروكو. (3) توثيق لكشف عن تاريخ التأسيس. نتيجة البحث: قضايا حفظ القرآن الكريم في معهد المقدسة فونوروكو هي: الكسل، مشكلات الطلاب بالمدرس، مشكلات الطلاب مع أصحابه، مشكلات الطلاب في منزله، حاجة الطلاب في المعهد غير التام. حل قضايا حفظ القرآن الكريم في معهد المقدسة فونوروكو هي: لابدّ المدرس ابداعي كي طلاب لا يكسل ف حفظ القرآن مثل عاقب المدرس لمن نائم أوناعس، أخرى بالحكاية الحافز كي لا ضجر، وجب على المدرس أن يأتي في وقت التام للإشراف طلاب في حفظ القرآن، لأنّ إذا تأخّر السيّد أولا يأتي أنّ طلاب سيعمل بنفسه لأنّ ليس هناك المراقب، لابدّ على كلّ طلاب أن يسامح الخطائات من أصحابه، حرام على كل والدين أن يخبر المشكلات في المنزل إلا بالضرورة، لابدّ لكل الوالد أن يتمّ حاجة ولده في المعهد.الكلمة الرائسية: القرآن، المدرس، الطالب، قضية، حلّ